SUSTAINABLE TOURISM DEVELOPMENT IN PROTECTED AREA: CASE OF CIKOLE FOREST RESERVE, WEST BANDUNG, INDONESIA - Maalim Mbarouk Maalim; Alhilal Furqan (ASEAN Journal on Hospitality and Tourism, 2019)
Sustainable tourism development (STD) is one of the current emerging vital issues. The aims of the paper are: to explore to what extent the development of tourism at Cikole Protected Area (PA), to identify the impacts of tourism practices, and to evaluate how tourism benefits to the stakeholders framed in the category of sustainability. Data were obtained through various sources like interviews, field observation and documentation, which utilized a multi-case study approach. Data were analyzed using thematic and coding. The findings, Cikole forest reserve has greatly provided positive image to the development of sustainable tourism and conservation of natural areas without destroying the main function of the forest as a source of livelihood, natural disaster prevention, and its surrounding environment of the community. However, there are also indications of unsustainable ways to some tourism destinations areas. The respective tourism stakeholders like planners, government organizations, environmentalists, private sectors, and communities, in particular, are important parts of tourism development through their involvement, participation, and decision-making process.